The Long-Lasting Effects of "Placebo Injections" in Knee Osteoarthritis: A Meta-Analysis. (December 2021) - Previtali, Davide; Merli, Giulia; Di Laura Frattura, Giorgio; Candrian, Christian; Zaffagnini, Stefano; Filardo, Giuseppe
Objectives: To quantify the placebo effect of intraarticular injections for knee osteoarthritis in terms of pain, function, and objective outcomes. Factors influencing placebo effect were investigated. Design: Meta-analysis of randomized controlled trials; Level of evidence, 2. PubMed, Web of Science, Cochrane Library, and grey literature databases were searched on January 8, 2020, using the string: (knee) AND (osteoarthritis OR OA) AND (injections OR intra-articular) AND (saline OR placebo) . The following inclusion criteria were used: double-blind, randomized controlled trials on knee osteoarthritis, including a placebo arm on saline injections. The primary outcome was pain variation. Risk of bias was assessed using the RoB 2.0 tool, and quality of evidence was graded following the GRADE (Grading of Recommendations Assessment, Development and Evaluation) guidelines. Results: Out of 2, 363 records, 50 articles on 4, 076 patients were included. The meta-analysis showed significant improvements up to the 6-month follow-up: Visual Analogue Scale (VAS)-pain −13.4 mean difference (MD) (95% confidence interval [CI]: −21.7/−5.1; P < 0.001), Western Ontario and McMaster Osteoarthritis Index (WOMAC)-pain −3.3 MD (95% CI: −3.9/−2.7; P < 0.001). Other significant improvements were WOMAC-stiffness −1.1 MD (95% CI: −1.6/−0.6; P < 0.001), WOMAC-function −10.1 MD (95% CI: −12.2/−8.0; P < 0.001), and Evaluator Global Assessment −21.4 MD (95% CI: −29.2/−13.6; P < 0.001). The responder rate was 52% (95% CI: 40% to 63%). Improvements were greater than the "minimal clinically important difference" for all outcomes (except 6-month VAS-pain). The level of evidence was moderate for almost all outcomes. Conclusions: The placebo effect of knee injections is significant, with functional improvements lasting even longer than those reported for pain perception. The high, long-lasting, and heterogeneous effects on the scales commonly used in clinical trials further highlight that the impact of placebo should not be overlooked in the research on and management of knee osteoarthritis.